A photographic image – between an archive and a semblance. Photographs in Tadeusz Różewicz’s The Professor’s Little Knife - Hanna Marciniak (Przestrzenie Teorii)
This article explores the issue of postmemory and secondary witnessing as dealt with in Tadeusz Różewicz’s 2002 poem The Professor’s Little Knife. The paper presents two photographs which refer to the problem of the Holocaust’s representation and its limits. The first picture comes from the collection of the U.S. Holocaust Memorial Museum; however, the author concealed its origins and changed its appearance so that it resembled a retro nude photograph. The second one is a raw, non-stylized picture of a knife that belonged to Professor Porębski during imprisonment in Auschwitz-Birkenau concentration camp. By using various interpretation methods, such as the deconstruction of an image or empathic reading, the author of this article examines the limits and consequences of treating a photograph as “spectral evidence”.